Synthesis Nanofiber PVA/Chitosan Using Electrospinning Method and Application for Gold Recovery - Dwi Sabda Budi Prasetya; Ahmadi Ahmadi; Dwi Pangga; Ari Dwi Nugraheni; Harsojo Harsojo; Edy Supriyanto; Habibi Habibi (Indonesian Review of Physics (IRiP), 2021)
This paper introduces a new process of gold recovery using nanofiber PVA/Chitosan from a gold-cyanide solution. Gold recovery in cyanide solution is made using nanofiber PVA/Chitosan produced with electrospinning technique. This research was conducted through several stages, 1) The designing of electrospinning tool, 2) Synthesis of nanofiber PVA/Chitosan with electrospinning technique, and 3) Gold recovery experiment using nanofiber PVA/Chitosan biosorption with the variations of initial concentration and time. The results showed that nanofiber PVA/Chitosan could be used as a gold ion absorber. The occuration of the isotherm process follows the Freundlich isotherm model, which is advantageous and occurs on a heterogeneous surface. From the results, it was agreed that nanofiber PVA/Chitosan is potential for gold recovery.